2014
DOI: 10.1080/13658816.2014.917646
|View full text |Cite
|
Sign up to set email alerts
|

An agent-integrated irregular automata model of urban land-use dynamics

Abstract: Urban growth models are useful tools to understand the patterns and processes of urbanization. In recent years, the bottom-up approach of geo-computation, such as cellular automata and agent-based modeling, is commonly used to simulate urban landuse dynamics. This study has developed an integrated model of urban growth called agent-integrated irregular automata (AIIA) by using vector geographic information system environment (i.e. both the data model and operations). The model was tested for the city of San Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 30 publications
(27 reference statements)
1
26
0
1
Order By: Relevance
“…O'Sullivan, 2001b;Dahal and Chow, 2015) and there have been successful attempts to employ irregular space representation in CA-based models (e.g. Hu and Li, 2004;Moreno et al, 2008;Dahal and Chow, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Sullivan, 2001b;Dahal and Chow, 2015) and there have been successful attempts to employ irregular space representation in CA-based models (e.g. Hu and Li, 2004;Moreno et al, 2008;Dahal and Chow, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As the aim of CA models is often to aid or improve urban planning, it would seem appropriate to adopt the same space representation as that used by urban planners. Early attempts to develop irregular CAbased models of land use change and urban growth have used cadastral parcels or similar types of space representation (Moreno et al, 2008;Pinto and Antunes, 2010;Lugo and Valdivia, 2012;Dahal and Chow, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The sitespecific assessment of the simulation results showed that the integration of the extended RL model is helpful for improving the predictive power of an ABM for residential land growth simulation. To evaluate the model performance further, the predicted pixels were categorized into perfect match, close match, and poor match with reference to the study by Dahal and Chow (2014). The perfect match category includes converted pixels in the predicted map that spatially agree with the developed area in the reference map.…”
Section: Experiments Results and Analysismentioning
confidence: 99%
“…With respect to cell-focused research, attempts have been made to adjust the regular grid. Researchers have applied the Voronoi and Delaunay methods to segment the research area, proposed the 'point-line plane' model to conceptualize CA, and used entities such as parcels, streets, and buildings to define cells (Perzy et al 2014, Dahal and Chow 2014. Finally, improvements in neighborhood-focused research have also gained popularity in recent years (Van Vliet et al 2009.…”
Section: Introductionmentioning
confidence: 98%